Choreographing Couch and Collimator in Volumetric Modulated Arc Therapy - Yang, Yingli; Zhang, Pengpeng; Happersett, Laura; Xiong, Jianping; Yang, Jie; Chan, Maria; Beal, Kathryn; Mageras, Gig; Hunt, Margie (International journal of radiation oncology, biology, physics, 2011)
To design and optimize trajectory-based, noncoplanar subarcs for volumetric modulated arc therapy (VMAT) deliverable on both Varian TrueBEAM system and traditional accelerators; and to investigate their potential advantages for treating central nervous system (CNS) tumors. To guide the computerized selection of beam trajectories consisting of simultaneous couch, gantry, and collimator motion, a score function was implemented to estimate the geometric overlap between targets and organs at risk for each couch/gantry angle combination. An initial set of beam orientations is obtained as a function of couch and gantry angle, according to a minimum search of the score function excluding zones of collision. This set is grouped into multiple continuous and extended subarcs subject to mechanical limitations using a hierarchical clustering algorithm. After determination of couch/gantry trajectories, a principal component analysis finds the collimator angle at each beam orientation that minimizes residual target–organ at risk overlaps. An in-house VMAT optimization algorithm determines the optimal multileaf collimator position and monitor units for control points within each subarc. A retrospective study of 10 CNS patients compares the proposed method of VMAT trajectory with dynamic gantry, leaves, couch, and collimator motion (Tra-VMAT); a standard noncoplanar VMAT with no couch/collimator motion within subarcs (Std-VMAT); and noncoplanar intensity-modulated radiotherapy (IMRT) plans that were clinically used. Tra-VMAT provided improved target dose conformality and lowered maximum dose to brainstem, optic nerves, and chiasm by 7.7%, 1.1%, 2.3%, and 1.7%, respectively, compared with Std-VMAT. Tra-VMAT provided higher planning target volume minimum dose and reduced maximum dose to chiasm, optic nerves, and cochlea by 6.2%, 1.3%, 6.3%, and 8.4%, respectively, and reduced cochlea mean dose by 8.7%, compared with IMRT. Tra-VMAT averaged beam-on time was comparable to Std-VMAT but significantly (45%) less than IMRT. Optimized couch, gantry, and collimator trajectories may be integrated into VMAT with improved mechanical flexibility and may provide better dosimetric properties and improved efficiency in the treatment of CNS tumors.